Grading Controversies in the Assessment of University Graduates in Bangladesh (Crossing the Border: International Journal of Interdisciplinary Studies, 2014)
Tertiary education has undergone several changes in the past few decades in Bangladesh. And one of the important alterations seems to be the introduction of letter grade system instead of numeric marking for assessment. Though letter grading as part of assessment is now an integral component of all the universities in Bangladesh, surprisingly this method of assessment is not consistent, even though the University Grants Commission (UGC) has provided a uniform grading scale to follow. This study attempts to find out the purposes of grading, problems with current grading practices and the impact of such discrete grading system on the learners and teachers. Finally, it suggests some ways out in order to bring harmony to the overall grading process. DOI: http://dx.doi.org/10.3126/ctbijis.v2i1.10813 Crossing the Border: International Journal of Interdisciplinary Studies Vol.2(1) 2014: 61-74